Tahapan Gerakan Terpadu Tabir Timur Berdayo (Gerdu Tatibo) oleh Pemerintahan Kecamatan dalam Memajukan Desa dengan Memperhatikan Kearifan Lokal pada Tahun 2019 - Siti Maryam; Hayatullah Hayatullah (Universitas Muara Bungo, 2023)
GERDU TATIBO is an East Tabir District Innovation program which runs in the field of Village and District government performance and develops it in order to advance or maximize the performance and results of government work in regulating government management and finances and focusing village funds on MSEs and the development of BUMDes to improve Village Paddy and the Economy in Villages, and the development of arts and cultural communities throughout East Tabir District as a means of promoting all products and potential in East Tabir District. Difficulty in accessing roads to reach villages, lack of public awareness in implementing the District Government Policy which has been detailed in the GERDU TATIBO Innovation Strategy, less than optimal administration and cooperation within both the sub-district and village governments, and so on from the background of this Innovation Strategy It was created so that researchers wanted to see how the